2017
DOI: 10.1038/ejhg.2016.178
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and behavioural impact of returning personal results from whole-genome sequencing: the HealthSeq project

Abstract: Providing ostensibly healthy individuals with personal results from whole-genome sequencing could lead to improved health and well-being via enhanced disease risk prediction, prevention, and diagnosis, but also poses practical and ethical challenges. Understanding how individuals react psychologically and behaviourally will be key in assessing the potential utility of personal whole-genome sequencing. We conducted an exploratory longitudinal cohort study in which quantitative surveys and in-depth qualitative i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
64
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 49 publications
6
64
0
Order By: Relevance
“…Participants with PDR results reported using slightly more emotional and problem-based coping than those without PDR but coping behaviors and actions were minimal in both groups. Overall, learning about a wide range of secondary findings (well beyond the ACMG list of secondary findings) appeared to have little measurable impact on most participants, which is consistent with previous reports (Lewis et al, 2016; S. C. Sanderson et al, 2017).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Participants with PDR results reported using slightly more emotional and problem-based coping than those without PDR but coping behaviors and actions were minimal in both groups. Overall, learning about a wide range of secondary findings (well beyond the ACMG list of secondary findings) appeared to have little measurable impact on most participants, which is consistent with previous reports (Lewis et al, 2016; S. C. Sanderson et al, 2017).…”
Section: Discussionsupporting
confidence: 86%
“…Participants displayed a tendency to overestimate the ability of genomics to predict disease risk and subsequent disappointment about the lack of overall results or of results related to a specific disease or trait, which has been documented in other genomic studies, suggesting a need to anticipate and manage unrealistic expectations of GS (Amendola et al, 2015; Lewis et al, 2016; S. C. Sanderson et al, 2017).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…We found that many participants experienced positive emotional reactions to receiving their risk results, similarly to other genetic testing studies . Sanderson et al . and Wasson et al .…”
Section: Discussionsupporting
confidence: 85%
“…Personal genomic testing is increasingly being offered in clinical, research and commercial contexts . The mainstreaming of genomic testing offers the possibility of providing personalized risk information for common, polygenic diseases such as melanoma on a population‐wide scale .…”
mentioning
confidence: 99%